Analisis Informasi Citra Anatomi Vaskular dengan Multi Planar Reformating (MPR) dan Maximum Intensity Projection (MIP) pada Fase Early Arteri Pemeriksaan MSCT Abdomen - Ratna Istiningrum; Fatimah Fatimah; Tri Wulanhandarini (Poltekkes Kemenkes Semarang, 2017)
Background: The development in the field of image reconstruction is growing rapidly along with the development of CT Scan. In the early stages of MSCT abdominal artery is usually found various kinds of vascular abnormalities such as stenosis, aneurism and others. Post processing image techniques commonly used include MPR and MIP. The purpose of this study is to determine whether there is a difference between MPR and MIP techniques and to know which one is better between the two.Methods: This research was quantitative study with experimental approach. The study was conducted at Bhakti Dharma Husada Surabaya Hospital with 15 samples by performing reconstruction on vascular anatomical image of coronal examination of abdominal MSCT. Assessment of anatomical information data is done by 2 respondents. Data analysis was done by kappa test followed by Wilcoxon sign rank test.Result : The results showed the difference between the post-processing of MIP and MPR on the coronal stages of the early arterial phase of the abdominal MSCT examination, based on the results of non-parametric statistical test analysis (Wilcoxon) showed a significant value of p value = 0.001. The result of MIP mean rank value (8,46) is higher than the mean rank value of MPR (1,50), it can be known that post proceeding MIP technique on coronal phase cuts early arterial examination of abdominal MSCT produces better anatomical image information.Conclusion: On examination of abdominal MSCT in the early arterial phase should be at the time of processing the image is also done by using post-processing MIP because more clearly than the MPR.